Various Types of Fetal Arrhythmias and Assessment of the Cardiac Function in a Fetus with a Cardiac Capillary Hemangioma: A Case Report - Koh, Jihye; Shin, Myung Shin; Han, Byeol; Lee, Jinha; Won, Hye-Sung (Perinatology (Online), 2024)
We present a case of fetal cardiac hemangioma that caused fetal arrhythmia and reduced ventricular contractibility. At 31 weeks and 1 day of gestation, a 29-year-old primiparous mother was referred to our institution due to an abnormal ultrasound finding, suspicious of a fetal cardiac mass occupying the right atrium (RA). The blood flow from the RA to the right ventricle (RV) was decreased. Additional evaluation through FetalHQ (GE Healthcare Korea) revealed diminished RV contractility. At gestational age 35 weeks and 1 day, the fetus had developed paroxysmal supraventricular tachycardia. We decided to perform an emergency cesarean section to prevent further impairment in fetal cardiac circulation. Postnatal echocardiography showed a pedunculated mass on the free wall of the RA, and the cardiac movements were affected with atrial flutter. Immediate mass excision was performed. Pathological analysis confirmed that the mass was a juvenile capillary hemangioma. The newborn stayed admitted for postoperative care and recovered healthy without any signs of cardiac arrhythmia. KCI Citation Count: 0